Applying FRBR model to bibliographic works on Al-Quran - Mansor, Yushiana; Sarif Abdullah, Sharifah Nur Amirah (Faculty of Computer Science and Information Technology, Universiti Malaya, 2015)
This study explores the feasibility of applying the object-oriented Functional Requirements for Bibliographic Records (FRBR) model to MARC-based bibliographic records on the Al-Quran. Based on the content analysis of 127 MARC-based bibliographic records on Al-Quran from the International Islamic University Malaysia (IIUM) OPAC system, this paper reports on the process of mapping FRBR entities to set of works on Al-Quran. The attributes of the bibliographic works in the MARC records were identified and grouped according to the FRBR entities. The findings suggest that, overall, most of the MARC-based bibliographic records on Al-Quran were sufficient to represent the FRBR model. However, several issues were identified as affecting the process of creating entity-relationship model for “FRBRizing” bibliographic works on Al-Quran. These include inconsistencies in romanizing records in Arabic scripts, difficulties in identifying complex works, missing fields for subject headings, and missing fields for record-object relationship identification. Thus, a major conclusion drawn is that the quality of MARC records is an important aspect in ensuring the bibliographic records are having complete, correct, and reliable data for FRBRization process.